The Relationship Between Learning Motivation and Student Engagement in Project-Based Learning - Lastri Utami; Muhammad Feriady; Diah Arumsasi (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2026)
Learning motivation plays a crucial role in fostering students’ active engagement throughout the instructional process. Economics instruction on the topic of wages in Grade XI at SMAN 2 Mranggen demonstrates low levels of student engagement when learning is conducted solely through theoretical, teacher-centered approaches. Students require an instructional model that is capable of simultaneously enhancing learning motivation and promoting active participation. This study aims to analyze the relationship between learning motivation and students’ learning engagement in Project-Based Learning (PjBL). A quantitative approach was employed, utilizing descriptive analysis and canonical correlation analysis. The findings indicate a strong and significant relationship between learning motivation and student engagement in project-based economics instruction, with a canonical coefficient of 0.839 in the first function. Multivariate analysis revealed significant results; however, partial correlations between individual variables did not demonstrate strong statistical significance. The learning motivation indicators showing the strongest relationships were perseverance in completing tasks and the ability to seek and solve problems. The most prominent indicators of learning engagement were listening activities and emotional activities. Descriptive analysis using word count of students’ responses to open-ended questionnaires concluded that student engagement was reflected in several key terms, namely: experiencing feelings of enjoyment, perceiving the learning as exciting, gaining broader insights, and improvement in public speaking skills. This study contributes to the enrichment of research on the relationship between learning motivation and learning engagement and serves as a foundation for teachers in designing innovative, contextual, and engagement-oriented economics instruction.